A presença de Kaiser no Quadro Teórico do Tratamento Temático da Informação (TTI) - Sales, Rodrigo de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The systematic indexing developed by the German librarian Julius Otto Kaiser at the end of the nineteenth and the beginning of the twentieth centuries brought groundbreaking contributions to the theoretical framework of the Subject Approach to Information (SAI). Neverthless, the SAI literature usually refers to Kaiser more through the subject analysis based on the concrete-process binomy than through the pioneering development of indexing as a method to construct indexes. This study addresses Kaiser as a theoretical reference in the SAI universe by proposing that Kaiser’s conception of systematic indexing established the pillars of the synthetic analytical methods, which, in turn, was the basis for the development of Ranganathan’s faceted classification. The theoretical framework on which this study is based is comprised by the literature produced by the Anglo-American approaches, namely bibliographic classification, subject cataloguing and indexing. To do so, we put Kaiser’s professional career in the SAI scenario, showing his theoretical dialogues with other exponents of the area, which set him on the same level as others such as Otlet, Cutter and Ranganathan. For our methodological approach, we adopted the pragmatism of William James – which focuses on taken paths and the possibilities of accomplishment –, we investigated how the systematic procedures of Kaiser’s indexing method can appear as a pioneer of the synthetic analytical method. Pragmatic observation was empirically supported by the analysis of Kaiser’s works, which constitute a crucial body of investigation. The analytical and synthetic dimension in Kaiser’s works allows the definition of variables used to relate his method with Ranganathan’s. Based on such variables (elements of the analysis, development of analysis, development of synthesis and the products... (Complete abstract click electronic access below)

A indexação sistemática desenvolvida pelo bibliotecário alemão Julius Otto Kaiser no final do Século XIX e início do Século XX trouxe contribuições pioneiras para a concepção do quadro teórico do Tratamento Temático da Informação (TTI). No entanto, Kaiser é, quando muito, abordado pela literatura da área mais pela análise de assuntos baseada no binômio concreto-processo do que pelo desenvolvimento pioneiro da indexação enquanto método de construção de índices. Dessa forma, o presente estudo resgata a figura de Kaiser como referencial teórico no universo do TTI a partir da proposição de que, ao elaborar sua indexação sistemática, Kaiser concebeu os pilares iniciais do método analítico sintético, que por sua vez, serviu de base para o desenvolvimento da teoria da classificação facetada de Ranganathan. O quadro teórico que subsidia o estudo é formado pela bibliografia produzida pela vertente anglo-americana de TTI, nomeadamente, a classificação bibliográfica, a catalogação de assuntos e a indexação. Para tanto, contextualizou-se a trajetória profissional de Kaiser no cenário do TTI, de modo a revelar suas interlocuções teóricas com expoentes da área, fato que o colocou lado a lado com nomes como Otlet, Cutter e Ranganathan. Adotando como abordagem metodológica o pragmatismo de William James, cujo foco recai nos caminhos percorridos e nas possibilidades de realização, investigou-se como a sistemática procedimental do método de indexação de Kaiser pode figurar-se como precursora do método analítico sintético. A observação pragmática foi respaldada empiricamente pela análise das obras de Kaiser, que consistem no corpus fundamental da investigação. As dimensões analítica e sintética extraídas das obras de Kaiser possibilitaram a definição dos elementos fundamentais (pontos de...
Keywords: Indexação; Classificação; Organização da informação; Information organization